Desain UI/UX Aplikasi SKCK Berbasis Mobile pada Sistem Siyanmin Ditintelkam - Supriyadi Supriyadi (Pusat Riset dan Inovasi Nasional, 2025)
Administrative Service Section Intelligence Directorate Polda Metro Jaya is is one of the sections of the Police of the Republic of Indonesia which is responsible for providing administrative services and supervision in the form of permission letters or statements concerning foreigners, firearms or explosives, social or political activities of the community, and SKCK for the community in need. On the implementation of the system in Siyanmin that is currently running it feels less effective because there are some problems. For example, the manufacturing process takes up to two days or more, then the data is not integrated in each unit, the SKCK requirement information in Polda is limited only as a pamphlet, and then the registration process of SKCK is manually, Making SKCK Without Following the Applicable Procedure, and There is an inconsistency of the payment data present in the Siyanmin unit in the payment validation process. Planning UI/UX Design Applications Mobile-based Police Registration in Administrative Service Section Intelligence Directorate Polda Metro Jaya so that the results of this design can help in so that in the presentation of information about the time of SKCK production can be presented effectively, efficiently and up to date.